Scooby-Doo!. Winter wonderdog [videorecording (DVD)] - Auberjonois, René, 1940-2019-; Buzzi, Ruth; Kasem, Casey; Messick, Don (Warner Home Video, 2002)
Scooby-Doo and the gang face off against festive frights, frosty nights, and the ghost of Christmas, who wants to wish everyone a scary Christmas! And the gang unwrap a series of mysteries in order to stop a group of chilling crooks from stealing the spirits of the season.